1998
DOI: 10.1007/s11661-998-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution during creep of single-phase gamma TiAl

Abstract: Mechanical experiments and transmission electron microscope (TEM) observations indicate that single-phase ␥-TiAl does exhibit primary, secondary, and inverse creep, but not steady-state creep. Constant stress creep tests of ␥-Ti-51Al-2Mn conducted at 550 ЊC, 597 ЊC, and 703 ЊC have been interrupted at different stages in the creep process. The TEM observations of these specimens were used to document the microstructural evolution that occurs during creep. Superdislocation motion was activated and subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At lower stresses (regime II), both n and Q C are nearly twice the values expected for climb -controlled creep. Primary creep is followed by a period with steadily increasing creep rate [38] . Again these fi ndings indicate that the creep rate in regime II is determined by mechanisms other than dislocation climb.…”
Section: Single -Phase γ (Tial) Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…At lower stresses (regime II), both n and Q C are nearly twice the values expected for climb -controlled creep. Primary creep is followed by a period with steadily increasing creep rate [38] . Again these fi ndings indicate that the creep rate in regime II is determined by mechanisms other than dislocation climb.…”
Section: Single -Phase γ (Tial) Alloysmentioning
confidence: 99%
“…Single -phase TiAl (Ti -51Al -2Mn) examined after secondary creep at (550 to 703) ° C exhibited superdislocations, faulted dipoles, pinned ordinary dislocation, and a modest number of twins [3,38] . Single -phase TiAl (Ti -51Al -2Mn) examined after secondary creep at (550 to 703) ° C exhibited superdislocations, faulted dipoles, pinned ordinary dislocation, and a modest number of twins [3,38] .…”
Section: Experimental Observation Of Creep Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Dislocation densities of usual metals and solid solutions that show normal primary creep behavior increase as the creep deformation proceeds within the primary creep regime [9]; single 7-TiA1 alloy also shows an increase of the dislocation density [10]. As for lamellar TiA1, the authors of the present investigation observed quantitatively that the dislocation density decreases significantly at the early stage of primary creep deformation under the conditions of 800~816/172-200MPa compared with undeformed specimens [1 l, 12].…”
Section: Introductionmentioning
confidence: 99%